Prosthetic rehabilitation of a patient with enucleated eye - a case report - Garg, P; Garg, S; Bansal, D; Suresh, S (Nepalese Journal of Ophthalmology, 2012)
Background: The loss of an eye has a crippling effect on the psychology of the patient, making rehabilitation process challenging for both doctor and patient. Objective: To report a case of anophthalmic socket with prosthetic rehabilitation in a cost effective manner. Case: A 32-year-old female presented with anophthalmic socket for prosthetic rehabilitation. A custom made ocular prosthesis was implanted successfully. Conclusion: The custom made ocular prosthesis is simple, affordable and can be carried out in a small clinical set-up and provides a superior natural appearance. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6550 Nepal J Ophthalmol 2012; 4 (2): 312-314